A numerical study of the circulation in the North-western Weddell Sea - Matano, Ricardo; Gordon, Arnold; Muench, R.; Palma, Elbio Daniel (Deep Sea Research Part II: Topical Studies in Oceanography)
An eddy-permitting simulation is used to study the circulation of the northwestern Weddell Sea and its interaction with the Scotia Sea. The analysis focuses on the circulation pathways, associated stratification, and volume transports. Comparison between model results and observations show reasonable agreements with respect to the modeled thermohaline stratification and circulation such as export of Weddell Sea Deep Water through the Weddell–Scotia Confluence region. Using the model results, we estimated the relative contributions of the two main routes of escape of the Weddell Sea deep waters into the Scotia Sea and the South Sandwich Trench. The main route for inter-basin exchange is found to be through the Scotia Sea (via the South Orkney Passage and the Bransfield Strait). Our simulation does not show advective transport of deep or bottom waters through the South Sandwich Trench, and Lagrangian analysis of float trajectories indicates that the fluxes in this region are more likely related to eddy-driven mixing than to mean flow advection. The model shows, in addition, some sub-basin scale features that have not been reported in the observations. The Weddell western boundary current is seen as a diffuse, filamentous feature. A southflowing jet was present over the outer shelf off the Antarctic Peninsula. Retroflection and return southward flow is seen for from the South Sandwich Trench, and there was a small inflow of Scotia Sea waters into the Powell Basin. Fil: Matano, Ricardo. Oregon State University; Estados Unidos Fil: Gordon, Arnold. Columbia University; Estados Unidos Fil: Muench, R. Earth–Space Research; Estados Unidos Fil: Palma, Elbio Daniel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto Argentino de Oceanografía. Universidad Nacional del Sur. Instituto Argentino de Oceanografía; Argentina. Universidad Nacional del Sur; Argentina